PENGARUH STRUKTUR KEPEMILIKAN DAN TATA KELOLA PERUSAHAAN TERHADAP KEBIJAKAN LIKUIDITAS PERUSAHAAN (Studi Empiris pada Perusahaan Nonkeuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2014) - Yogy Rahman; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
The aim of this research is to analyze the effect of ownership structures and corporate governance to corporate liquidity policy. Ownership structures used in this research are managerial ownership, institutional ownership, and foreign ownership. While the corporate governance mechanism used includes board of commissioners’ size, independent board proportion, board of directors’ size, and audit committee size.This research used annual report of non-finance companies listed in Indonesia Stock Exchange (IDX) 2012-2014. The sampling method in this research is purposive sampling, with the number of samples are 766 samples. Data analysis was performed with descriptive statistics, classical assumption and hypothesis testing of regression method using SPSS 23.The empirical result of this study shows that independent board proportion and managerial ownership are negatively and significantly affected to corporate liquidity policy. The result also shows that board of commissioners’ size, and board of directors’ size are positively and significantly affected to corporate liquidity policy. While the other variables such as the audit committee size, institutional ownership and foreign ownership are not significantly affected to corporate liquidity policy. This research also find that the control variables which are firm size and dividend payout ratio have significant effect to corporate liquidity policy.